Effects of the 2016 CDC opioid prescription guidelines on opioid use and worker compensation case length in patients with back pain - Alvarado, Anthony M.; Chung, Ethan; Deutsch, Harel (Acta neurochirurgica, 2023)
Background Narcotic consumption in the workers’ compensation population contributes to prolonged case duration, worse clinical outcomes, and opioid dependence. In 2016, the CDC provided recommendations guiding clinicians on prescribing opioids to adult patients with chronic pain. The objective of our study was to evaluate a cause-and-effect relationship between narcotic consumption and worker compensation claim length before and following guideline revision. Methods An administration database was retrospectively queried to identify patients evaluated for spine-related workers’ compensation claimants from 2011 to 2021. Data was recorded for age, sex, BMI, case length, narcotic usage, and injury location. Cases were grouped together by exam date before (2011–2016) and after (2017–2021) the 2016 CDC opioid guideline revision. Results Six hundred twenty-five patients were evaluated. Males composed 58% of the study population. From 2011 to 2016, narcotic consumption was reported in 54% of subjects versus no narcotic consumption in 46% of subjects (135 cases). From 2017 to 2021, narcotic consumption decreased to 37% ( P = 0.00298). Prior to the guideline revision, mean case length was 635 days. Following CDC guideline revision, there was a significant decline in mean case length duration to 438 days (31% reduction) ( P = 0.000868). Conclusion This study demonstrates that following revised opioid prescription recommendations by the CDC in 2016, there was a statistically significant decline in opioid consumption and workers’ compensation case length duration. Opioid use may influence prolonged worker disability and delayed return to work.